Quiet time observations of He ions in the inner magnetosphere as observed from the RBSPICE instrument aboard the Van Allen Probes mission. Issue 4 (19th February 2014) - Gerrard, Andrew; Lanzerotti, Louis; Gkioulidou, Matina; Mitchell, Donald; Manweiler, Jerry; Bortnik, Jacob
<x xml:space="preserve">Abstract</x> He ions contribute to Earth's ring current energy and species population density and are important in understanding ion transport and charge exchange processes in the inner magnetosphere. He ion flux measurements made by the Van Allen Probes Radiation Belt Storm Probes Ion Composition Experiment (RBSPICE) instrument are presented in this paper. Particular focus is centered on geomagnetically quiet intervals in late 2012 and 2013 that show the flux, L‐shell, and energy (65 keV to 518 keV) morphology of ring current He ions between geomagnetic storm injection events. The overall He ion abundance during the first nine months of RBSPICE observations, the appearance of a persistent high energy, low L‐shell He ion population, and the temporal evolution of this population all provide new insights into trapped ring current energy He ions. These data provide a unique resource that will be used to provide verifications of, and improvements to, models of He ion transport and loss in Earth's ring current region.